Disorders of volition - Sebanz, Natalie; Prinz, Wolfgang, 1942- (MIT Press, 2006)
Philosophers, psychologists, neuroscientists, and psychiatrists examine the will and its pathologies from theoretical and empirical perspectives, offering a conceptual overview and discussing schizophrenia, depression, prefrontal lobe damage, and substanc.